Modelling, simulation and control of a class of hybrid dynamic systems: using hybrid automaton, APROS and mixed integer quadratic optimisation algorithm. (7th June 2019) - Belazreg, Mohamed Fouzi; Halbaoui, Khaled; Boukhetala, Djamel; Boulheouchat, Mohamed El-Hadi
This paper presents modelling, simulation and control of a class of hybrid dynamic systems. Hybrid automaton is used for modelling a transition system with continuous dynamics. The framework consists of a finite set of state and transition for modelling a discrete dynamics called control mode. Each control mode describes continuous dynamics. Using APROS tools, it permits to simulate the behaviour of the hybrid system approaching in the experiment case: actuators, pumps and valves. Mixed logic dynamics formalism allows to describe the dynamics defined by logic rules, continuous dynamics and constraints. These are described by linear dynamic equations subject to linear inequalities involving continuous, discrete and auxiliary variables. This model is used to synthesise a predictive control law under constraints. The controller requires online mixed-integer quadratic programming solution to an optimisation problem. Simulation was performed to illustrate performances and efficiency of these methods and tools.